Evaluasi Kemampuan Guru dalam Pengembangan Tes Pilihan Ganda di SDN Rawa Buaya 05 Petang Jakarta Barat - Ina Magdalena; Riska Septiana Soleha; Siti Rukoyah; Syamsul Hidayah; Muflihatun Nufus (RC-INSTITUT, 2020)
The 2013 curriculum caused a change in school learning so teachers must accept and be able to adapt well. With changes like this the teacher must also evaluate each lesson, evaluation is a teacher measuring tool used to measure the ability of students in the cognitive, affective, and psychomotor domains. One measuring tool used by teachers to measure students' reasoning is the multiple-choice form test instrument. The development of multiple-choice test instruments conducted by teachers often finds a problem for both low grade and high-grade teachers. The aim of this research is to find out the constraints experienced by low and high-grade teachers during the development of multiple-choice test instruments and the ability of teachers in developing multiple-choice test instruments. This is a type of qualitative research that uses a qualitative descriptive approach. The population in this study is Elementary Schools in Indonesia, namely SDN Rawa Buaya 05 Petang which has implemented the 2013 curriculum.